PERAN PEMERINTAH DALAM PENANGANAN EKSPLOITASI PEKERJA MIGRAN INDONESIA DI SINGAPURA - Kustiawan; Ikhlasunnisa Samara, Raenanta; Febri Widyanti Rangkuti; Sri Rejeki Asih Purba; Frisma Yunita; Savira Felisia (Jurnal Dialektika Politik, 2024)
The objective of this scientific paper is to examine and understand the role of the government in addressing the exploitation of Indonesian migrant workers in Singapore. The research method used is a qualitative descriptive approach. The results indicate that the government's role in handling the exploitation of Indonesian migrant workers in Singapore is functioning effectively. This is evident in the government's policies, which include the issuance of various legal instruments ranging from the constitution to its implementing regulations, and engaging in bilateral, regional, and multilateral cooperation with other countries, especially the destination countries for Indonesian migrant workers. Additionally, the government, with the help of non-governmental organizations (NGOs) both local, national, and international, community organizations, and individuals, continuously provides education, training, and legal protection assistance to Indonesian migrant workers.